Improved xylose and arabinose utilization by an industrial recombinant Saccharomyces cerevisiae strain using evolutionary engineering - Garcia Sanchez, Rosa (BioMed Central, 2010)
BACKGROUND: Cost-effective fermentation of lignocellulosic hydrolysate to ethanol by Saccharomyces cerevisiae requires efficient mixed sugar utilization. Notably, the rate and yield of xylose and arabinose co-fermentation to ethanol must be enhanced. RESULTS: Evolutionary engineering was used to improve the simultaneous conversion of xylose and arabinose to ethanol in a recombinant industrial Saccharomyces cerevisiae strain carrying the heterologous genes for xylose and arabinose utilization pathways integrated in the genome. The evolved strain TMB3130 displayed an increased consumption rate of xylose and arabinose under aerobic and anaerobic conditions. Improved anaerobic ethanol production was achieved at the expense of xylitol and glycerol but arabinose was almost stoichiometrically converted to arabitol. Further characterization of the strain indicated that the selection pressure during prolonged continuous culture in xylose and arabinose medium resulted in the improved transport of xylose and arabinose as well as increased levels of the enzymes from the introduced fungal xylose pathway. No mutation was found in any of the genes from the pentose converting pathways. CONCLUSION: To the best of our knowledge, this is the first report that characterizes the molecular mechanisms for improved mixed-pentose utilization obtained by evolutionary engineering of a recombinant S. cerevisiae strain. Increased transport of pentoses and increased activities of xylose converting enzymes contributed to the improved phenotype.